Islamic Education as a Means of Strengthening Tolerance Among Religious Communities - Ahmad Suprayitno (Badan Usaha Milik Desa Berkaho Pungpungan, 2026)
Islamic education plays a strategic role in fostering attitudes of tolerance among religious communities within plural societies. However, despite extensive discussions on Islamic education and tolerance, there is still limited integrative analysis examining how Islamic education can systematically strengthen tolerant character amid contemporary social polarization. This article aims to analyze the concept, implementation, and challenges of strengthening Islamic education as a means of shaping tolerant character through a literature review approach. The discussion emphasizes that Islamic education is not only oriented toward spiritual and intellectual aspects but also toward social dimensions that cultivate values of justice, empathy, and respect for differences. The implementation of tolerance values is carried out through curriculum integration, educators’ role modeling, inclusive educational environments, innovative learning methods, and community-based social activities. On the other hand, Islamic education faces challenges in the form of digital social polarization, limited curriculum integration, insufficient pedagogical capacity of educators, minimal cross-community collaboration, and suboptimal utilization of technology. Analysis using the grand theory perspective of structural functionalism indicates that education functions as a mechanism for maintaining social order and harmony. The findings highlight that strengthening tolerance-based Islamic education contributes to shaping moderate and religious individuals while supporting the stability of multicultural societies. With an adaptive and comprehensive approach, Islamic education can serve as an agent of peace and social integration.